Richness and Abundance of Soil Seed Bank in Dif ferent Agroecosystems in Central Veracruz, Mexico - Pérez-Vázquez, Arturo; Castro-Jose, Carlos Nahin; del Angel-Pérez, Ana Lid; de la Cruz Vargas-Mendoza, Mónica (REVISTA TERRA LATINOAMERICANA, 2024)
The soil seed bank is key to plant succession. However, agricultural activities have had a great impact on the vegetation and its composition. The aim was to determine the soil seed bank in dif ferent grazing agroecosystems in the central part of Veracruz state, Mexico. Richness, abundance, diversity, equity, dominance and similarity of the species were quantified and compared among four agroecosystems (silvopastoral, pasture-trees, traditional grazing, and Acahual or secondary vegetation) in Veracruz, Mexico during the year 2017. Samples were collected. of soil at two depths (0-5, > 5-10 cm). A statistical dif ference was found in the seed bank (P < 0.05) in silvopastoral at both depths, 0-5 (H’ = 2.13) and 5-10 (H’ = 1.86). Equity and dominance were higher for this agroecosystem (0.86) and for Acahual (0.58) with statistical dif ferences (P < 0.05). No statistical dif ferences were found at sites between depths (P > 0.05). Similarity was greater than 50% at all sites and increased with soil depth. The evidence suggests that the greatest diversity of the seed bank was in silvopastoral from 0 to 5 cm deep. The seed bank has potential for the restoration of vegetation, mainly herbaceous, and can promote the development of shrubs and trees, despite the management of cattle ranching sites.